.NET programming : a practical guide using C♯ - Tapadiya, Pradeep K. (Pradeep Kumar), 1964- (Hewlett-Packard professional books., 2002)
Enterprise-class .NET programming in C#-from a developer's perspective. Internals of the .NET Framework-learn to get the most from its services Build professional applications using C#-quickly and efficiently Hands-on approach covering the Base Class Library, Remoting, ASP .NET Web Services, concurrency, security, enterprise services, dealing with legacy code, and much more .NET developers need more than buzzwords to get the job done. To tackle enterprise-class projects, they need both a real understanding of the .NET architecture and a working knowledge of how to put its services to work. In .NET Programming: A Practical Guide Using C#, .NET authority Pradeep Tapadiya takes a straightforward, hands-on approach to explain everything you need to know from development to deployment and maintenance for this platform-all from a developer's perspective. Using C# as the primary language, and with plenty of code examples throughout, this book is an excellent way to learn: The .NET infrastructure-packaging and deployment, the common language runtime and its services, and the .NET Framework class libraries Distributed computing-develop object-remoting applications for intranets and Web services for the Internet How to develop thread-safe code using the .NET synchronization infrastructure and learn asynchronous programming Interoperability with native DLLs and COM applications How to develop secure applications using role-based security and enforce security for third-party applications using code access permissions Enterprise services-develop scalable applications, support transactions, and more. Appropriate for experienced developers, .NET Programming will help you get the most from the .NET architecture-today.